Исследование АКЗ ВВЭР-1000 при разных программах регулирования енергоблоком - Цисельська, Т. О. (Видавництво Львівської політехніки, 2011)
The core-well by WWER-1000 at the variableб regime of power energy at different regulating programs is investigated from notion of axial stability at changing technological parameters. The most effective program of regulation providing comprehensible stability of axial offset at change of reactor power from 80 % to 100 % is defined.
Keywords: активна зона; ВВЕР-1000; енерговиділення; аксіальний офсет; реактивність; потужність